2021
DOI: 10.1177/15385744211028738
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Artery Dissection and Retroperitoneal Hemorrhage in Median Arcuate Ligament Syndrome Treated With a Stent and Transcatheter Arterial Embolization: Preprocedural 4-Dimensional Computed Tomography Angiography Assessment

Abstract: A 61-year-old man presented with retroperitoneal hemorrhage caused by an aneurysm rupture of the pancreaticoduodenal arcade (PDA), and acute celiac artery dissection distal to celiac axis stenosis. Owing to the gradual growth of the false lumen, we planned to deploy a stent to the celiac artery dissection and embolize the PDA aneurysm. Prior to stent placement, we assessed the acute celiac artery dissection distal to the stenosis using four-dimensional computed tomography (CT) angiography through expiration/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…4D-CTA is a non-invasive angiography technique that can quickly acquire cerebrovascular anatomical images and generate 3D images to observe target blood vessels from multiple perspectives. In addition, 4D-CTA has a temporal dimension based on 3D-CTA, so it can achieve real-time observation of morphological changes in the vascular wall in different phases of the cardiac cycle [11]. Cui et al [12] showed that 4D-CTA performed well in the diagnosis of intracranial aneurysms, showing high diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…4D-CTA is a non-invasive angiography technique that can quickly acquire cerebrovascular anatomical images and generate 3D images to observe target blood vessels from multiple perspectives. In addition, 4D-CTA has a temporal dimension based on 3D-CTA, so it can achieve real-time observation of morphological changes in the vascular wall in different phases of the cardiac cycle [11]. Cui et al [12] showed that 4D-CTA performed well in the diagnosis of intracranial aneurysms, showing high diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…症例1では,循環動態が安定していたことからTAEを第一選択としたが,脾動脈の屈曲・蛇行と狭小化が著しく,不完全塞栓となり最終的に手術を要した。ISCADの解離が脾動脈へ進展した結果解離性脾動脈瘤を形成し,さらに脆弱性の高い偽腔に急性膵炎の炎症が波及し破裂を来し,仮性動脈瘤を形成したものと考えられた。ISCADそのものの成因として膵炎が背景となっていたかに関しては報告が存在しない。症例2は,MALSに続発したISCADが脾動脈に進展し,解離性脾動脈瘤の形成から破裂に至った症例であった。MALSがISCADの発生に関与した症例は過去に報告されており,MALSに腹腔動脈解離が合併し膵十二指腸動脈瘤破裂に至った例 9)や,MALSに腹腔動脈解離を伴い血管内治療を施行した例 10),および血管内治療に加え腹腔鏡による弓状靭帯切離を施行した例 11)の3症例のみが存在している。MALSからISCADを生ずる機序は,腹腔動脈起始部の物理的狭小化によって血管内腔の圧上昇を来し,内膜と中膜の解離を生じるためと考えられる。無症候性のMALSが多く存在することは知られており,剖検例の検討では約1/3にMALSによる腹腔動脈圧迫を認めたとの報告もある 12), 13)。また,CTなどの画像検査で約7%に腹腔動脈の無症候性狭窄が発見されたとの報告もある 14)。ゆえに,症例2のように無症候性のMALSにISCADを潜在的に有している例も少なからず存在する可能性がある。なお,CTでISCADが偶発的に見つかった場合でも,循環動態が安定しており破裂や仮性動脈瘤を伴っていない場合にはルーチンでの血管造影は不要であり,MDCTでの形態的評価と経時的な経過観察で十分と考える。症例2ではTAEを第一選択としたが,もし仮に初期輸液にて循環動態の安定化が得られなかった場合,CT撮像ができないまま外傷性腹腔内出血として開腹止血術を先行させていた可能性があり,その場合ISCADによる内因性の解離性脾動脈瘤破裂との診断がつかなかった可能性がある。このように内臓動脈瘤破裂は,発症様式や全身状態においても選択される治療法が異なる病態であり,施設のリソースや各科のバックアップ体制なども考慮し,個々の施設で最適な止血方法を選択する必要があると考える。血管内治療,外科的治療のいずれを選択するにしても,初療を担う救急医がリーダーとして治療方針を決定し,専門的治療につなげることが要求されるため,内因性腹部出血の鑑別の一つとして常にこのような病態を念頭に置く必要がある。…”
Section: 考  察unclassified